Navigating the police promotion system: a comparison by gender of moving up the ranks. (2nd September 2020) - Drew, Jacqueline M.; Saunders, Jason
ABSTRACT: Promotion systems form a fundamental pillar in the development of organisational leadership capability. Surprisingly, little empirical research focus has been directed towards the specific decision-making processes of officers that influence their participation and engagement in the police promotion system. Importantly, gender differences must be examined as female police now represent the biggest demographic change in the pool of potential police leaders. Based on a study of police officers employed in one Australian state police jurisdiction, the research concludes that similar factors are generally associated with engagement with the police promotion system regardless of gender. Notably, gender differences only exist for factors related to support of higher-ranking officers in the promotion application process, support of colleagues once promoted, confidence in readiness for promotion, increased work hours and child/elder care difficulties and change in remuneration. The research highlights that gender equity policies designed to encourage female participation/engagement may result in unintended, negative consequences. Almost 80% of male officers in this study strongly indicating that females are promoted based on gender rather than skills and experience. The research has significant implications for police agencies who seek to support female officers moving into leadership positions.